HAK-HAK PEREMPUAN DAN TRADISI BELIS: STUDI KOMPARATIF DI SUMBA, ALOR, DAN LEMBATA, NUSA TENGGARA TIMUR - Gabriel Durah Langoday; Arwanto Harimas Ginting (Jurnal Politik Pemerintahan Dharma Praja, 2025)
This research examines belis as a marriage tradition in East Nusa Tenggara by comparing the belis tradition in three regions, namely Lembata, Alor and Sumba. The research focuses on the belis tradition, including the ritual system, the use of items used as belis, and the meaning of belis by the community. This research analyzes how the belis tradition forms a social norm that places women in a lower social class and strengthens the position of men in the family and social environment of the NTT community. Data collection in this research uses the literature study method by reviewing secondary data such as books, articles, journals, and all forms of reports that are in accordance with the issues raised. The results of this study show that the belis tradition has a major impact on the rights and position of a woman in the life of the NTT community. This research highlights how belis strengthens the position of men by placing men as the center of power and authority in the household and community, while women both in the household and social life will always be in a lower social class.